Jemaat Laodikia (Wahyu 3:14-22) Sebuah Tinjuan dari Bahasa Yunani - Chia, Philip Suciadi (Jurnal Teologi dan Pelayanan Kerusso, 2024)
The congregation of Laodicea stands out as the sole assembly within the Book of Revelation that does not receive commendation from Christ. This article undertakes an examination of various factors contributing to the lack of praise bestowed upon the Laodicean congregation by Christ, employing a linguistic analysis encompassing Greek syntax, aspect, and aktionsart. Through a detailed exploration of these linguistic dimensions, insights into the theological implications surrounding the Laodicean community's portrayal in Revelation are elucidated, shedding light on its significance within the broader narrative of the text.